EPIDEMEOLOGICAL PROFILE OF SICKLE CELL DISEASE PREVALENT IN CHHATTISGARH, CENTRAL INDIA - PK PATRA; SK PANIGRAHI; G BANERJEE (International Journal of Pharma and Bio Sciences, 2013)
330 clinically suspected sickle cell disease (SCD) patients admitted to Dept. of Pediatrics, Medical College & Hospital, Raipur (Chhattisgarh) between 9 months to 14 years of age within the time period of May 2000 to September 2007 were chosen as subjects for this study. The diagnosis of SCD was confirmed by Sodium Metabisulphite method. On the basis of the results of electrophoresis the subjects were divided into two groups’ i.e. Sickle Cell Anaemia (SCA) consisting of 195 patients and Sickle cell Trait (SCT) consisting of 135 patients. Detailed clinical examination, complete blood count, peripheral blood smear, bilirubin estimation, USG whole abdomen & digital radiograms of skull &limbs were done for every subject. Weakness is the commonest symptom followed by bone pain, abdominal pain, jaundice & fever respectively in decreasing order of prevalence. Pallor is the commonest sign followed by splenomegaly, lymphadenopathy, hepatomegaly & icterus respectively in the study population. When compared with incidences of clinical features &complications of SCD obtained from the studies on people of other parts of Indian sickle cell belt central Indian SCA are having worst features.